Description of COVID-19 patients admitted in an intensive care unit in the Seychelles Islands
@font-face font-family:"Times New Roman"; @font-face font-family:"宋体"; @font-face font-family:"Arno Pro"; @font-face font-family:"Arial"; p.p0 margin:0pt; margin-bottom:0,0001pt; margin-bottom:0pt; margin-top:0pt; font-size:10,5000pt; font-family:’Times New Roman’; p.p15 margin-bottom:0pt; margin-top:0pt; layout-grid-mode:char; color:rgb(0,0,0); font-size:12,0000pt; font-family:’Arno Pro’;